(untitled) (Research, Society and Development, 2021)
Objective: To analyze the palatal rugae patterns of a young Brazilian adults’ group, to classify this sample using the rugoscopic technique, as well as to evaluate possible differences between age group, skin color, use of orthodontic braces and oral surgeries in those surveyed. Material and Methods: Observational, classificatory, and transversal study, with a quantitative approach to palate wrinkles. The convenience sample was obtained from 30 female university students from a Dentistry course at a private educational institution. Data collection was performed using intraoral photographs of each participant’s palate, highlighting palatal wrinkles with the help of Microsoft Paint®, with subsequent classification of the images by a single researcher. For the classification of the university student’s palatine wrinkles, the method proposed by Carrea (1937) was taken into account. The data were analyzed statistically using the Chi-Square, Fischer Exact and Likelihood Ratio tests (p=0.05). Results: There was a predominance of women aged 19 to 22 years (70.0%), white (83.3%), who used an orthodontic appliance (83.3%) and denied having undergone any type of oral surgery (56.7%). The study identified seven to 18 palatine wrinkles, with different shapes. Conclusion: There was a higher incidence of wrinkles directed in different directions (type IV). Palatal rugoscopy did not result in characterizations with age, ancestry and use of orthodontic braces. However, there was a significant association between the rugoscopic profile of the university students evaluated and previous oral surgeries.